PARADIGMA PENELITIAN DALAM STUDI PENDIDIKAN ISLAM - Anwar Sadad; Zaharani; Ridwan; Putri Rahmadani; Witri; Anita; Nirwana; Ahmad Basori; Miftahurizik; Tison Haryanto; Ahmad Zaki; Suprihatin; Nur Anisyah (STKIP Subang, 2026)
Islamic education research has developed significantly in response to the increasingly complex educational, social, cultural, and technological challenges of the modern era. Consequently, selecting an appropriate research paradigm has become a fundamental aspect of producing scientific findings that are valid, relevant, and accountable. This paper aims to examine the concept, characteristics, and implementation of research paradigms in Islamic education studies, including the positivist, interpretive, critical, and transformative paradigms. The study employs a qualitative approach using a library research method by analyzing various scientific books, journal articles, and other relevant academic sources. The findings reveal that each research paradigm possesses distinct philosophical assumptions concerning ontology, epistemology, methodology, and axiology, which consequently influence research design, data collection techniques, data analysis, and the interpretation of findings. In the context of Islamic education, research paradigms should not only emphasize scientific rigor but also integrate Islamic values derived from the Qur'an and Sunnah. Such integration enables researchers to generate comprehensive knowledge that addresses educational issues while promoting ethical values, character development, and social justice. Therefore, researchers in Islamic education are expected to select research paradigms that align with the nature of the research problem and contribute to the advancement of Islamic educational theory and practice. This study provides theoretical insights that may serve as a reference for students, academics, and researchers in understanding and applying appropriate research paradigms within the field of Islamic education.